Afforestation for the Provision of Multiple Ecosystem Services: A Ukrainian Case Study - Maria Nijnik; Arie Oskam; Anatoliy Nijnik (International Journal of Forestry Research)
This paper presents an economic analysis of the planting of trees on marginal lands in Ukraine for timber production, erosion prevention, and climate mitigation. A methodology combining econometric analysis, simulation modelling, and linear programming to analyse the costs and benefits of such afforestation has been adopted. The research reveals that, at discount rates lower than 2%, establishment of new forests is economically justified in the majority of forestry zones. Incorporating the effects of afforestation on mitigating climate change increases social benefits. However, the results indicate that whilst soil protection benefits to agriculture from afforestation in the Steppe are expected to be high, carbon sequestration and timber production activities in the Steppe are cost inefficient due to low rates of tree growth and relatively high opportunity costs of land. The opportunity costs of land are also high in the Polissja where afforestation is cost inefficient at 2% and higher discount rates.